Settlers of Unassigned Lands - McLeod, Charles (Ann Arbor University of Michigan Press, 2015)
In these seven stories spanning the Midwest to California, Charles McLeod brings us characters estranged from their homelands and locked in conflict with their past and present selves. In (3z(BHow to Start Your Own Midwestern Ghost Town,(3y (Ban unnamed narrator hatches a plan to capitalize on rural decay. A porn star trying to transition to the mainstream does an interview with a German reporter in (3z(BThe Subject of Our First Issue Is Art.(3y (BIn the title story, a closeted heroin dealer follows a ghostly girl into an Oakland graveyard. And in (3z(BRancho Brava,(3y (Bthe conductor of a focus group about corporate salsa keeps getting interrupted by visitors from the Old West. Alternating between the comic, the tragic, and the neurotic$1 (Band often all three at once$1 (BMcLeod$1 (Bs second collection transports readers from the American mainstream to the dark edges of cities and the heartland$1 (Bs lost, forgotten towns, into the lives of people trying to decipher if they can escape their pasts, and at what cost.s
English
Keywords: Short stories; Fiction